Analisis Penerapan Penalti pada Pencaiaran Deposito Mudharabah Sebelum Jatuh Tempo di Bank Aman Syariah - Dian Widia Asmerianti; Haris Santoso (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2026)
Mudharabah deposits are a fund collection product in sharia banking which is carried out based on a cooperation agreement between the customer as shohibul maal and the bank as mudharib with a profit sharing system. This product has a certain period of time so that funds cannot be withdrawn before maturity. However, in practice there are still customers who withdraw their deposits before they are due, because of the urgent need to anticipate this, Sharia safe banks implement a penalty policy as a consequence of contract violations. This research aims to analyze the application of penalties for disbursement of mudharabah deposits before maturity and assess the effectiveness of penalties in preventing customers' decisions to withdraw funds early. This research uses a qualitative method with a descriptive approach through interview techniques, observation and documentation. The research results show that penalties function as a control for customers not to withdraw deposits before maturity, but are not always the main consideration in customer decision making when faced with urgent economic needs.